Impact of Pollution from Coal on the Anemic Status of Children and Women: Evidence from India - Gaurav Datt; Pushkar Maitra; Nidhiya Menon; Ranjan Ray; Sagnik Dey; Sourangsu Chowdhury (Institute of Labor Economics (IZA), 2020)
Economic growth in emerging market economies has come hand-in-hand with growing demand for energy, with many of them meeting this higher demand by increased use of coal to fuel electricity generation. This paper examines the impact of pollution generated by coal fueled power units on the anemic status of children and women in India. We show that among very young children (aged 0–5 years), the number of coal units in the district in the month and year of birth significantly increases the likelihood of being anemic net of a comprehensive set of child, mother, household and district level controls. Exposure in utero matters as well for child anemia, while the number of coal plants in the district also induce greater anemia among adult women. Impacts on anemic status are driven by the growth of PM2.5 pollution attributable to emissions from coal-powered units. We undertake a series of falsification and specification checks to underline the robustness of our results. Our research adds anemia to the list of significant health costs of relying on coal-fired power generation in meeting the increasing demand for energy that emerging market economies like India face.
Keywords: I15; Q32; Q53; O12; 330; anemia; coal units; PM2.5; air pollution; children; women; India